Hubungan Pengetahuan Masyarakat dengan Stigma Terhadap Penderita TB Paru Diwilayah Kerja Puskesmas Bandar Jaya Lampung Tengah - Dewa Ayu Neli Elvania; Eka Trismiyana; Rudi Winarno (Universitas Malahayati Lampung, 2023)
ABSTRACT According to the 2020 WHO global TB report, Indonesia is one of the countries in the world with the third highest TB rate. The most common cause of death world wide in 2015 was tuberculosis. From the Big Indonesian Dictionary, stigma is a negative trait in a person due to environmental influences. According to research conducted by Courtwright and Tumer (2010), said that the stigma associated with tuberculosis can cause delays in treatment and have a negative impact on the continuity of treatment for TB clients. It is known that there is a relationship between community knowledge and the stigma of pulmonary TB sufferers in the community. Type of quantitative research, cross-sectional approach. The population of the community in the working area of the Bandar Jaya Health Center is 325 families. Sample 179 respondents. The sampling technique was purposive sampling. Questionnaire data collection techniques. Bivariate analysis, Chi Square test. Based on the frequency of good knowledge there are 58.1% of respondents and 41.9% of respondents are not good. Based on the frequency of positive stigma 32.4% of respondents and negative 67.6% of respondents. The p- value = 0.007 (≤ 0.05%) with an Odd Ratio of 1.768 is obtained. There is a relationship between community knowledge about pulmonary TB and community stigma against pulmonary TB sufferers in the Bandar Jaya Central Lampung Working Area in 2023 (p-value = 0.007). It is hoped that the public can increase their knowledge by seeking the right information, such as coming to health workers and actively participating in prevention programs for pulmonary tuberculosis so that it does not discriminate against sufferers. Keywords: Knowledge, Stigma, Pulmonary TB ABSTRAK Menurut laporan Tb global World Health Organizaion (WHO) tahun 2020, Indonesia adalah salah satu negara didunia dengan tingkat Tuberkulosis (TBC) tertinggi ketiga. Penyebab kematian paling umum di seluruh dunia pada tahun 2015 adalah tuberkulosis. Dari kamus besar Bahasa Indonesia stigma adalah ciri negatif pada seseorang karena pengaruh lingkungan. Menurut penelitian yang dilakukan Courtwright and Tumer (2010), mengatakan bahwa stigma pada penyakit tuberkulosis dapat menyebabkan keterlambatan pengobatan dan berdampak negatif terhadap kelangsungan berobat pada klien TBC. Diketahui hubungan antara pengetahuan masyarakat dengan stigma terhadap penderita TB Paru yang berada dimasyarakat. Jenis penelitian kuantitatif pendekatan cross-sectional. Populasi masyarakat di wilayah kerja puskesmas Bandar Jaya sebanyak 325 KK dengan sampel 179 responden dengan teknik pengambilan sampel purposive sampling, teknik pengumpulan data menggunakan quesioner. Analisis Bivariat, uji Chi Square. Berdasarkan frekuensi pengetahuan baik terdapat 58,1% responden dan kurang baik 41,9% responden. Berdasarkan frekuensi stigma positif 32,4% responden dan negatif 67,6% responden. Didapatkan nilai p-value = 0,007 (≤ 0.05 %) dengan Odd Ratio 1,768. Ada hubungan pengetahuan masyarakat tentang TB paru dengan stigma masyarakat terhadap penderita TB paru di Wilayah Kerja Bandar Jaya Lampung Tengah tahun 2023 (p-value = 0,007). Diharapkan Masyarakat dapat meningkatkan pengetahuan dengan cara mencari informasi yang tepat seperti datang ke tenaga kesehatan dan ikut aktif dalam program pencegahan terhadap penyakit Tb paru sehingga tidak menyebabkan diskriminasi pada penderita. Kata Kunci: Pengetahuan, Stigma, TB Paru